Perovskite catalyst for catalytic combustion of methane as well as preparation method and application of perovskite catalyst

The preparation of perovskite catalysts through ionizing radiation technology solves the problems of complexity and easy agglomeration of traditional methods, and realizes low-cost and high-catalytic activity catalyst preparation, which is suitable for industrial applications of methane catalytic combustion.

CN119819309AActive Publication Date: 2025-04-15NANJING TECH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411934769.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-15
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The preparation method of traditional perovskite catalysts is complex and prone to agglomeration after roasting, which limits its large-scale application in the industrial field.

Method used

The perovskite catalyst is prepared by ionizing radiation technology. After ultrasonic stirring, the alkaline solution is added to adjust the pH, irradiation reaction is carried out, centrifugal washing, drying and calcining, and a catalyst with amorphous, small particle size, large specific surface area and abundant pores and defects are obtained.

Benefits of technology

A simple and repetitive preparation method of perovskite catalyst is realized, which reduces material costs and improves the catalytic activity of the catalyst. It is suitable for methane catalytic combustion and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819309A_ABST
    Figure CN119819309A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite catalyst for methane catalytic combustion and a preparation method and application thereof. The method comprises the following steps: dissolving different nitrates with the same amount of substance in water, ultrasonically stirring, adding an alkaline solution, adjusting to alkalescence, treating for a period of time by ionizing radiation, and centrifugally washing and drying to obtain the high-purity nitrate. And roasting in an air atmosphere to obtain the non-crystallized perovskite catalyst with small particle size, large specific surface area and abundant pores and defects. The radiation method is simple in process, low in equipment requirement, low in energy consumption, high in repeatability and capable of achieving large-scale industrial preparation, and in addition, the catalyst is low in cost, high in catalytic activity, suitable for the field of environmental catalysis such as methane catalytic combustion and the like and good in industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalytic combustion environmental protection, and in particular to a perovskite catalyst for methane catalytic combustion and a preparation method and application thereof. Background Art

[0002] Methane (CH4) is the second most powerful greenhouse gas after carbon dioxide (CO2). It comes from a variety of sources, including coal, oil and gas production, agriculture and waste disposal. Although methane has an atmospheric lifetime of only a dozen years, its potential warming power is more than 80 times that of CO2 and contributes about 30% to global warming.

[0003] Catalytic combustion technology is a green, economical and environmentally friendly method for removing CH4. It can operate effectively at lower CH4 concentrations and can completely convert CH4 at lower temperatures to achieve NO x The core of catalytic combustion technology is the catalyst, and the selection of effective catalyst plays a key role in effectively eliminating CH4.

[0004] Precious metal catalysts, including Pt, Pd, Rh and Ir, have been widely studied due to their low ignition temperature and high specific surface area, with well-established preparation methods and reaction mechanisms. However, their high cost and easy deactivation at high temperatures have hindered their widespread application. In contrast, perovskite, as a type of composite metal oxide, has the characteristics of low price, good stability and adjustable structure, and is expected to become an ideal catalytic material for catalytic methane removal.

[0005] However, due to the high preparation cost, the traditional perovskite catalyst synthesis methods, such as the sol-gel method, are mostly used in the field of scientific research and are difficult to be widely promoted in large-scale industrial production. The precipitation method is to add precipitants and inhibitors to the metal alkoxide to regulate the reaction rate, and then go through drying, roasting and other processes to obtain the finished product. The precipitants commonly used in this method, such as solvents such as ammonia, citric acid, and ethanolamine, will pollute the environment, the solvent recovery work is quite challenging, and the biosafety is low. These defects make the precipitation method face many difficulties in the process of industrial production. The hydrothermal method is to carry out the reaction in a special closed high-pressure reactor. During the production, parameters such as reaction time, temperature and pH value need to be precisely controlled. However, the cerium oxide produced by this method is prone to more serious agglomeration, which undoubtedly adds safety hazards to industrial production and limits its large-scale application in the industrial field. Therefore, it is of great significance to develop a preparation method for perovskite catalysts that is suitable for large-scale preparation and repeatability. Summary of the invention

[0006] In view of the problems of complex preparation process and easy agglomeration after calcination of traditional catalysts, the present invention proposes a method for preparing a perovskite catalyst for catalytic combustion of methane. The preparation method of the present invention is simple and easy to repeat, and the material cost is low. The obtained catalyst has the advantages of amorphization, small particle size, large specific surface area, abundant pores and defects, etc.

[0007] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:

[0008] A method for preparing a perovskite catalyst for catalytic combustion of methane, specifically comprising: weighing nitrate A and nitrate B according to equal amounts of substances and dissolving them in water, stirring them uniformly by ultrasonication, adding an alkaline solution to adjust the mixed solution to weak alkalinity, using ionizing radiation to carry out irradiation reaction, centrifugally washing and drying, and calcining the dried solid in an air atmosphere to obtain a perovskite catalyst, denoted as ABO3, wherein the metal A in the nitrate A is one or more of rare earth metal La, rare earth metal Ce, alkaline earth metal Sr or alkaline earth metal Ca, and the metal B in the nitrate B is one or more of transition metal Co, transition metal Ni, transition metal Mn or transition metal Fe.

[0009] Preferably, the concentration of the alkaline solution is 1-3 mol / L.

[0010] Preferably, the alkaline solution is NaOH, NaHCO3 or Na2CO3 solution.

[0011] Preferably, the weak alkalinity of the mixed solution is 8-9.5.

[0012] Preferably, the ionizing radiation source is 60 Co-gamma ray, X-ray or electron accelerator.

[0013] Preferably, the absorbed dose range of the irradiation reaction is 50-500 kGy, and the duration is 24-72 h.

[0014] Preferably, the calcination temperature is 500-800°C and the calcination time is 2-4h.

[0015] The perovskite catalyst prepared by the above preparation method has the characteristics of amorphization, small particle size, large specific surface area, abundant pores and defects.

[0016] Application of the perovskite catalyst prepared by the above preparation method in catalytic combustion of methane.

[0017] Preferably, the concentration of methane in the application is 0.5-2 vol.%, and the space velocity is 10000-30000 L / (kg·h).

[0018] Beneficial effects:

[0019] Compared with the prior art, the method for preparing a perovskite catalyst for catalytic combustion of methane in the present invention has the following advantages:

[0020] (1) The present invention uses radiation technology to prepare perovskite catalysts, improving the material's advantages such as amorphization, small particle size, large specific surface area, abundant pores and defects.

[0021] (2) The preparation process of the present invention is suitable for large-scale production and has strong repeatability.

[0022] (3) The catalyst of the present invention is a low-cost perovskite material and has high activity in catalytic combustion of methane, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD spectra of CeNiO3 perovskite catalysts prepared in Example 2 and Comparative Example 2 of the present invention, wherein (1) is Example 2, and (2) is Comparative Example 2;

[0024] Figure 2 The SEM images of CeNiO3 perovskite catalysts prepared in Example 2 and Comparative Example 2 of the present invention, wherein (1) is Example 2, and (2) is Comparative Example 2;

[0025] Figure 3 The catalytic combustion activity curves of CeNiO3 perovskite catalysts prepared in Example 2 and Comparative Example 2 of the present invention for methane, wherein (1) is Example 2 and (2) is Comparative Example 2. DETAILED DESCRIPTION

[0026] The present invention is described in detail through the following specific examples. It should be understood that these specific examples are only used to illustrate and explain the present invention, and do not constitute any limitation to the scope of the present invention.

[0027] Example 1

[0028] 4.3301g La(NO3)2·6H2O and 2.9103g Co(NO3)2·6H2O were weighed and dissolved in 200mL deionized water. After ultrasonic stirring, 3mol / L Na2CO3 solution was added to adjust the pH of the mixed solution to 9. An electron accelerator was used as an ionizing radiation source. The irradiation reaction was carried out for 24h at an absorbed dose range of 200kGy. After centrifugal washing and drying, it was calcined in an air atmosphere at 500℃ for 2h to obtain LaCoO3 catalyst. The specific surface area of ​​the catalyst was characterized and analyzed by N2-sorption-desorption, and the specific surface area of ​​LaCoO3 was measured to be 15.1m 2 / g.

[0029] 0.1g LaCoO3 catalyst was mixed with 0.3g quartz sand and added to a quartz tube with an inner diameter of 8mm in a continuous flow fixed bed. The methane concentration in the feed gas was 0.5vol.%, and the air velocity was 20000L / (kg·h). -1 The temperature was raised to 800°C at a rate of 1.5°C. When the methane conversion rate was 90%, the reaction temperature was 638°C.

[0030] Example 2

[0031] Weigh 4.3422g Ce(NO3)2·6H2O and 2.9079g Ni(NO3)2·6H2O and dissolve them in 200mL deionized water. After ultrasonic stirring, add 1mol / L NaOH solution to adjust the pH of the mixed solution to 8. 60 Co-γ rays were used as the ionizing radiation source, and the irradiation reaction was carried out for 36 hours at an absorbed dose range of 100 kGy. After centrifugal washing and drying, the catalyst was calcined in an air atmosphere at 550°C for 3 hours to obtain a CeNiO3 catalyst.

[0032] The test results are as follows:

[0033] Figure 1 (1) is the XRD spectrum of the CeNiO3 perovskite catalyst prepared by the radiation method in Example 2. After comparison with the standard spectrum, Figure 1 All characteristic peaks in (1) are compared with the standard spectrum of CeNiO3 Figure 1 The results show that the prepared product is CeNiO3, and the diffraction peak intensity is stronger, indicating that the radiation treatment of the catalyst can form a better perovskite crystal phase structure.

[0034] Figure 2 (1) is a SEM image of the CeNiO3 perovskite catalyst prepared by the radiation method in Example 2. It can be seen from the figure that the CeNiO3 prepared by the radiation method has smaller particles and more defects. The specific surface area of ​​the catalyst was characterized and analyzed by N2-sorption-desorption. The results showed that the CeNiO3 prepared by the radiation method has a large specific surface area (20.6 m 2 / g), which is conducive to the full contact between the catalyst and the reactant molecules, thereby accelerating the catalytic reaction.

[0035] 0.1g CeNiO3 catalyst was mixed with 0.3g quartz sand and added to a quartz tube with an inner diameter of 8mm in a continuous flow fixed bed. The methane concentration in the feed gas was 1vol.%, and the air velocity was 10000L / (kg·h). -1 The temperature was raised to 800°C at a rate of 1.5 ℃. Figure 3As shown in FIG. 1 , (1) is the activity curve of the CeNiO3 perovskite catalyst prepared in Example 2 for catalytic combustion of methane. It can be seen that the T 90 (representing the temperature corresponding to 90% methane conversion) is significantly lower (585°C), indicating that the radiation-prepared catalyst CeNiO3 exhibits better catalytic activity.

[0036] Example 3

[0037] 2.1163g Sr(NO3)2 and 3.579g Mn(NO3)2 solution (50wt.%) were weighed and dissolved in 200mL deionized water. After ultrasonic stirring, 2mol / L NaHCO3 solution was added to adjust the pH of the mixed solution to 8.5. X-rays were used as ionizing radiation sources and irradiated for 72h at an absorbed dose range of 500kGy. After centrifugal washing and drying, the mixture was calcined in an air atmosphere at 600℃ for 4h to obtain a SrMnO3 catalyst. The specific surface area of ​​the catalyst was characterized and analyzed using N2-sorption-desorption, and the specific surface area of ​​SrMnO3 was measured to be 16.5m 2 / g.

[0038] 0.1g SrMnO3 catalyst was mixed with 0.3g quartz sand and added into a quartz tube with an inner diameter of 8mm. The methane concentration in the raw gas was 1.5vol.%, and the space velocity was 30000L / (kg·h). -1 The temperature was raised to 800°C at a rate of 1.5°C. When the methane conversion rate was 90%, the reaction temperature was 620°C.

[0039] Example 4

[0040] Weigh 4.3301g La(NO3)2·6H2O and 2.9079g Ni(NO3)2·6H2O and dissolve them in 200mL deionized water. After ultrasonic stirring, add 2mol / L NaOH solution to adjust the pH of the mixed solution to 9.5. Use an electron accelerator as an ionizing radiation source and irradiate for 48h at an absorbed dose range of 400kGy. After centrifugal washing and drying, calcine at 650℃ in air atmosphere for 4h to obtain LaNiO3 catalyst. The specific surface area of ​​the catalyst was characterized and analyzed by N2-sorption-desorption, and the specific surface area of ​​SrNiO3 was measured to be 13.8m 2 / g.

[0041] 0.1g LaNiO3 catalyst was mixed with 0.3g quartz sand and added into a quartz tube with an inner diameter of 8mm. The methane concentration in the raw gas was 0.5vol.%, and the air velocity was 10000L / (kg·h). -1The temperature was raised to 800°C at a rate of 1.5°C. When the methane conversion rate was 90%, the reaction temperature was 605°C.

[0042] Example 5

[0043] 4.3422g Ce(NO3)2·6H2O and 2.9103g Co(NO3)2·6H2O were weighed and dissolved in 200mL deionized water. After ultrasonic stirring, 3mol / L Na2CO3 solution was added to adjust the pH of the mixed solution to 8.8. X-rays were used as ionizing radiation sources and irradiated for 36h at an absorbed dose range of 300kGy. After centrifugal washing and drying, the mixture was calcined at 700℃ in air atmosphere for 3h to obtain CeCoO3 catalyst. The specific surface area of ​​the catalyst was characterized and analyzed by N2-sorption-desorption, and the specific surface area of ​​CeCoO3 was measured to be 17.3m 2 / g.

[0044] 0.1g CeCoO3 catalyst was mixed with 0.3g quartz sand and added to a quartz tube with an inner diameter of 8mm. The methane concentration in the raw gas was 2vol.%, and the air velocity was 20000L / (kg·h). -1 The temperature was raised to 800°C at a rate of 1.5°C. When the methane conversion rate was 90%, the reaction temperature was 631°C.

[0045] Example 6

[0046] 2.1163g Sr(NO3)2 and 4.04g Fe(NO3)3·9H2O were weighed and dissolved in 200mL deionized water. After ultrasonic stirring, 2mol / L NaHCO3 solution was added to adjust the pH of the mixed solution to 9.2. X-rays were used as the ionizing radiation source and the irradiation reaction was carried out at an absorbed dose range of 50kGy for 60h. After centrifugal washing and drying, the mixture was calcined in an air atmosphere at 800℃ for 2h to obtain SrFeO3 catalyst. The specific surface area of ​​the catalyst was characterized and analyzed by N2-sorption-desorption, and the specific surface area of ​​SrFeO3 was measured to be 12.6m 2 / g.

[0047] 0.1g SrFeO3 catalyst was mixed with 0.3g quartz sand and added to a quartz tube with an inner diameter of 8mm. The methane concentration in the raw gas was 1.5vol.% and the air velocity was 20000L / (kg·h). -1 The temperature was raised to 800°C at a rate of 1.5°C. When the methane conversion rate was 90%, the reaction temperature was 625°C.

[0048] Comparative Example 1

[0049] Referring to Example 1, the Na2CO3 solution was not added to adjust the pH of the mixed solution to obtain a 1-LaCoO3 catalyst, and then the same application test was performed. The specific surface area of ​​LaCoO3 was measured to be 13.4 m 2 / g.

[0050] 0.1g 1-LaCoO3 catalyst was mixed with 0.3g quartz sand and added into a quartz tube with an inner diameter of 8mm. The methane concentration in the raw gas was 1.5vol.%, and the air velocity was 20000L / (kg·h). -1 The temperature is raised to 800°C at a rate of 1.5°C. When the methane conversion rate is 90%, the reaction temperature is 750°C.

[0051] Comparative Example 2

[0052] Referring to Example 2, a 2-CeNiO3 catalyst was obtained without using an ionizing radiation source, and then the same application test was carried out.

[0053] The test results are as follows:

[0054] Figure 1 (1) is the XRD spectrum of the CeNiO3 perovskite catalyst prepared without radiation in Comparative Example 2. After comparison with the standard spectrum, Figure 1 All characteristic peaks in (1) are compared with the standard spectrum of CeNiO3 Figure 1 The results show that the prepared product is CeNiO3. Figure 1 Compared with (1), the diffraction peak intensity is weaker, indicating that the perovskite formed without radiation treatment has lower crystallinity.

[0055] Figure 2 (2) is a SEM image of the CeNiO3 perovskite catalyst prepared without radiation in Comparative Example 2. It can be seen from the image that it has larger particles and fewer defects. The specific surface area of ​​the catalyst was characterized and analyzed using N2-sorption-desorption. The results showed that CeNiO3 prepared without radiation had a smaller specific surface area (14.8 m 2 / g), which is not conducive to the full contact between the catalyst and the reactant molecules, hindering the catalytic reaction.

[0056] 0.1g 2-CeNiO3 catalyst was mixed with 0.3g quartz sand and added into a quartz tube with an inner diameter of 8mm. The methane concentration in the raw gas was 1.5vol.%, and the air velocity was 10000L / (kg·h). -1 The temperature was raised to 800°C at a rate of 1. Figure 3 (2) is the activity curve of the CeNiO3 perovskite catalyst prepared in Comparative Example 2 for catalytic combustion of methane. It can be seen that the T 90It is significantly higher, indicating that the catalyst CeNiO3 prepared without radiation exhibits worse catalytic activity (764°C).

[0057] Comparative Example 3

[0058] Referring to Example 3, 3-SrMnO3 catalyst was obtained without calcination, and then the same application test was carried out. The specific surface area of ​​the catalyst was characterized and analyzed by N2-sorption-desorption. The specific surface area of ​​SrMnO3 was measured to be 14.9 m 2 / g.

[0059] 0.1g 3-SrMnO3 catalyst was mixed with 0.3g quartz sand and added into a quartz tube with an inner diameter of 8mm. The methane concentration in the raw gas was 1.5vol.%, and the air velocity was 30000L / (kg·h). -1 The temperature was raised to 800°C at a rate of 1.5°C, and the reaction temperature was 789°C when the methane conversion rate was 90%.

[0060] The results of the above examples and comparative examples are summarized in Table 1 below.

[0061] Table 1 Methane conversion of different catalysts in programmed temperature oxidation test

[0062]

[0063] As can be seen from Table 1, the preparation method of a perovskite catalyst for methane catalytic combustion of the present invention has the advantages of simple process, low equipment requirements, low energy consumption and strong repeatability. Compared with the plasma treatment technology mentioned in the prior art, which has poor processing accuracy and uniformity, safety hazards and environmental pollution, high cost and limited processing range, the present invention has the advantage of realizing large-scale industrial preparation, and the catalyst has low cost and high catalytic activity, is suitable for environmental catalysis fields such as methane catalytic combustion, and has good industrial application prospects.

Claims

1. A method for preparing a perovskite catalyst for catalytic combustion of methane, characterized in that: The preparation method is specifically as follows: weighing nitrate A and nitrate B according to equal amounts of substances and dissolving them in water, stirring them evenly by ultrasonication, adding alkaline solution to adjust the mixed solution to weak alkalinity, using ionizing radiation to carry out irradiation reaction, centrifuging and washing, and calcining the dried solid in an air atmosphere to obtain a perovskite catalyst, denoted as ABO3, wherein the metal A in the nitrate A is one or more of rare earth metal La, rare earth metal Ce, alkaline earth metal Sr or alkaline earth metal Ca, and the metal B in the nitrate B is one or more of transition metal Co, transition metal Ni, transition metal Mn or transition metal Fe.

2. The method for preparing a perovskite catalyst for catalytic combustion of methane according to claim 1, characterized in that: The concentration of the alkaline solution is 1-3 mol / L.

3. The method for preparing a perovskite catalyst for catalytic combustion of methane according to claim 1, characterized in that: The alkaline solution is NaOH, NaHCO3 or Na2CO3 solution.

4. The method for preparing a perovskite catalyst for catalytic combustion of methane according to claim 1, characterized in that: The weak alkalinity of the mixed solution is 8-9.

5.

5. The method for preparing a perovskite catalyst for catalytic combustion of methane according to claim 1, characterized in that: The ionizing radiation source is 60 Co-gamma ray, X-ray or electron accelerator.

6. The method for preparing a perovskite catalyst for catalytic combustion of methane according to claim 1, characterized in that: The absorbed dose range of the irradiation reaction is 50-500 kGy, and the duration is 24-72 hours.

7. The method for preparing a perovskite catalyst for catalytic combustion of methane according to claim 1, characterized in that: The calcination temperature is 500-800°C and the calcination time is 2-4h.

8. The perovskite catalyst prepared by any one of the preparation methods of claims 1 to 7, characterized in that: The perovskite catalyst has amorphization, small particle size, large specific surface area, and abundant pores and defects.

9. Use of the perovskite catalyst prepared by any one of the preparation methods of claims 1 to 7 in catalytic combustion of methane.

10. The use according to claim 9, characterized in that: In the application, the concentration of methane is 0.5-2 vol.%, and the space velocity is 10000-30000 L / (kg·h).

Citation Information

Patent Citations

  • Method for preparing methyl hydride combustion catalyst

    CN101293201A

  • Preparation method of perovskite thin film photoelectric device based on electron irradiation modification

    CN111640868A

  • Nanoscale ceramic plasma catalyst for stabilizing and assisting plasma combustion

    CN115335144A

  • Method for preparing oxygen-defect-rich perovskite material through ionizing radiation

    CN117839708A

  • Synthesis of plasma generating - chemical looping catalysts

    WO2021145843A2